2020
DOI: 10.3390/nu12020517
|View full text |Cite
|
Sign up to set email alerts
|

Ready-Made Oral Nutritional Supplements Improve Nutritional Outcomes and Reduce Health Care Use—A Randomised Trial in Older Malnourished People in Primary Care

Abstract: Large trials assessing oral nutritional supplements (ONS) and dietary advice (DA) in primary care are lacking. This study examined effects of ONS + DA versus DA on intake, weight, QoL, healthcare use and satisfaction in malnourished free-living older people. Three hundred and eight people (71.5 ± 10.7y) were randomised to receive ONS + DA (n154) or DA (n154) for 12 weeks. At baseline, 4, 8, 12 weeks, intake, weight, QoL, healthcare use and satisfaction were measured. ONS + DA group (mean daily intake ONS 480 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“… 38 In support, a randomized, controlled trial in the UK specifically examined use of ONS plus dietary advice to treat older undernourished people living in the community. 39 Results showed that nutrition care reduced visits to healthcare providers, lowered the frequency of ED visits, and shortened length of stay when hospitalization was needed. 39 Use of ONS as part of nutrition care has been shown to improve health outcomes and cut costs in the hospital, 40 in home-care services, 23 and in the community.…”
Section: Discussionmentioning
confidence: 99%
“… 38 In support, a randomized, controlled trial in the UK specifically examined use of ONS plus dietary advice to treat older undernourished people living in the community. 39 Results showed that nutrition care reduced visits to healthcare providers, lowered the frequency of ED visits, and shortened length of stay when hospitalization was needed. 39 Use of ONS as part of nutrition care has been shown to improve health outcomes and cut costs in the hospital, 40 in home-care services, 23 and in the community.…”
Section: Discussionmentioning
confidence: 99%
“…adding a slice of ham; adding cheese to soup). Fortification was combined with ONS to achieve higher enrichment levels in some older people, particularly in very small eaters (23,24). However, for very small eaters (calorie and/or protein ratios < 66%), meal enrichment was not sufficient to compensate for their nutritional deficit.…”
Section: Discussionmentioning
confidence: 99%
“…49 In another study among 308 primary care malnourished patients, ONS for 12 weeks and dietary advice were superior to dietary advice alone in decreasing health care use (visits, emergency admissions, and length of stay) and improving the quality of life. 50 Moreover, 3-months therapy with ONS in 80 malnourished patients with benign digestive diseases has improved muscle function and the quality of life. 51 In ACLD patients, Iwasa et al have reported that nutritional counseling compared with no counseling improved the long-term survival of ACLD patients.…”
Section: Adherence and Outcomementioning
confidence: 99%